Compare to ultrastructure of root of resistant and susceptible oriental lily clones by Fusarium oxysporum f. sp. lilii. (December 2018) - Zhang, Yi-Ping; Qu, Su-Ping; Yang, Xiu-Mei; Xu, Feng; Zhang, Li-Fang; Wang, Ji-Hua; He, Yue- Qiu
Abstract: The production of lily bulbs and flowers is under serious threat from basal rot of the bulbs caused by the soil-borne fungus Fusarium oxysporum f.sp. lilii . Oriental lily hybrid 'Casa Blanca' resistant clones to Fusarium oxysporum f.sp. lilii was available by toxin screening. To explore disease-resistance based on the cytology, colonization processes in the resistant oriental lily clones following inoculation with Fusarium oxysporum f.sp. lilii were studied prepared by transmission electron microscopy for ultra section preparation. Samples of susceptible clones and selected resistant clones were collected before inoculation and 3–6 days after inoculation and processed following conventional procedures. Before inoculation, from the ultrastructure of the cells and tissues, more starch grains in selected resistant somaclones and less starch grains in susceptible somaclones. After inoculation, from the ultrastructure of the cells and tissues, selected disease-resistant clone mainly in terms of resistance to extension mechanism is better than susceptible somalclones. Less number of hyphae found in disease-resistant clone cells. Resistant clone cells have a large number of degradable material and secretion, thus preventing fungus extension ability stronger. All of these results showed that Fusarium oxysporum after the invasion of disease-resistant clones is greatly hindered further expansion of the process.